DESAIN TRAFO CORELESS MENGGUNAKAN VIZIMAG - -, Uminingsih (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
This paper describes a simulation of coreless transformer design using Vizimag which is a software application tool for computation based on finite element method. The objective of this research is to study the effect of the coreless transformer parameters through the secondary output voltage such that it is hoped the optimal design to be achieved. Method is done by determining parameters which affect to coreless transformer such as frequency and coupling coefficient as variable to be simulated. Primer of transformer has diameter and height of solenoid of 50 cm and 30 cm with 11 winding, input voltage of 20 kV where as secondary of transformer has diameter and height of solenoid of 194 cm and 40 cm with 970 winding, these all are determined as constant parameters. The results of simulation show that the placement of primer solenoid in the secondary solenoid affects deeply to secondary voltage and to coupling coefficient. In addition frequency affects deeply to secondary voltage where by increasing the frequency it will increase secondary voltage until reaching optimum voltage. In position of primer solenoid in the centre of secondary solenoid and frequency higher than 90 kHz, the optimum simulation design of coreless transformer is achieved which are secondary voltage of 489 kV, coupling coefficient of 28,4%, and overall power efficiency of 0,71%.